Analisis Rasio Keuangan pada Koperasi Unit Desa (KUD) Panca Satya di Kecamatan Dawan Kabupaten Klungkung - ANDANI, LUH PUTU SUKMA; RANTAU, I KETUT; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.3, Juli 2015, 2016)
Abstract Analysis of Financial Ratios Cooperatin Village Unit (KUD) Panca Satya at Dawan Subdistrict, Klungkung Regency As integral part of national economic arrangement, the cooperation have strategic position and role in order to grow public economic potency. Since relased Inpres number 18 in 1998, The KUD do not as single cooperation at subdistrict level. Government program to develop villager like distribution of fertilizer, seed and suply of paddy at this time conducted via KUD. This study aims to find out the financial ratio of KUD Panca Satya Dawan in 2009 until 2013 viewed from financial aspect and financial situation by using financial ratio like: liquidity ratio, solvability ratio and profitability ratio affecting the financial performance of this KUD were also determined. The kind of data collected data qualitative and quantitative. Data collection method used observation, interview, documentation, and the literature study. Based on financial analysis, liquidity ratio and profitability was moderate, solvability ratios was bad. Horizontal analysis viewed from sheet balance and calculation of SHU show was good. Vertical analysis measured by using balance sheet and calculation of SHU tend improvement and fluctuation. Based on this research it can be suggested is KUD of Panca Satya Dawan should improve its performance to reach maximal profit and more improve their service. Decrease of solvability can be overcome by decrease its debt. Keywords: financial ratio, analysis of horizontal vertical